Islamic Spiritual (Rohis) Activities in Preventing and Overcoming Student Radicalism in School Institutions - Zafi, Ashif Az; Assegaf, Abd Rachman; Kailani, Najib (EDUKASIA, 2022)
This study aims to discover the reasons for the culture of peace instilled in Islamic spiritual (rohis) activists and the role of rohis activists in cultivating a culture of peace. This field research took place in SMA Negeri 1 Purworejo. This qualitative research seeks to describe the data from the field related to the discussion. This research focuses on the implementation of rohis activities. To get the data, data collection techniques were conducted through observation, interviews, and documentation. All data were then analyzed in stages: reducing the data, presenting the data, and concluding the research results. Meanwhile, the data validity was checked by triangulation in two modes: multiple sources and methods. This study concluded that (1) the reasons for instilling the character of a culture of peace in rohis activists is that the teachings of Islam practiced are intolerant and contradict the values taken from the history of the school. (2) The role of rohis activists in cultivating a culture of peace was carried out in two steps, i.e., preventing the entry of intolerance and constructing new knowledge. This construction of new knowledge was conducted by internalizing the attitude of a culture of peace. The method was done using lectures, practice, and dialogue.